Effectiveness of F18+ Fimbrial Antigens Released by a Novel Autolyzed Salmonella Expression System as a Vaccine Candidate against Lethal F18+ STEC Infection - Won, Gayeon; Lee, John H. (Frontiers in Microbiology, 2016)
Porcine edema disease (ED) caused by Shiga toxin 2e producing Escherichia coli expressing F18ab+ fimbriae (F18ab+STEC) frequently occurs in post-weaned piglets, resulting in significant economic loss in swine industries worldwide. In the present study, we proposed an effective prevention scheme against ED in which the attenuated Salmonella Typhimurium inactivated by the E gene mediated cell lysis to deliver target antigens, FedF and FedA, which function in fimbrial-mediated adhesion and as a major subunit of F18ab+fimbriae, respectively. The co-expression of FedA and FedF protein with outermembrane protein A signal peptide was confirmed in the resultant strains JOL1460 and JOL1464 by immunoblot analysis. Immunization with the candidate strains in mice led to the significant generation of immunoglobulin (Ig) G, specific to both antigens and secretory IgA specific to FedF (P < 0.05). The titers of IgG isotypes, IgG1 and IgG2a, used as markers for T-helpers (Th)-2 and Th-1 lymphocytes, respectively, also significantly increased in the immunized group (P < 0.05). The increase in CD3+CD4+ T lymphocyte subpopulation and in vitro proliferative activity was observed in in vivo stimulated splenocytes, which indicated the immunostimulatory effect of the candidate strains. Moreover, the immunized mice were completely protected from a lethal challenge against wild-type F18+ETEC whereas 28% of mice died in the non-immunized group. This study demonstrated that the inactivated Salmonella system can efficiently express and release FedF and FedA and induce robust immune responses specific to the target antigens, which is sufficient to protect the mice from the lethal challenge.